RANCANG BANGUN SISTEM INFORMASI SURAT PERINTAH PERJALANAN DINAS PADA SEKRETARIAT DAERAH PROVINSI BERBASIS WEB - Evi Ana Kusuma Lestari; Sri Endang Anjarwani; Nadiyasari Agitha (Journal of Computer Science and Informatics Engineering (J-Cosine), 2018)
Currently the Regional Secretariat of NTB have not specific applications which help to support the trip of the governance in conducting the business trip. The reason of the Regional Secretary of NTB wants to have a business trip information system because it still using a simple manual recording with the help of Micrososoft Exel and business trip reports are not able to provide detailed infotmation. To achieve this, required software development process in the form of an information system of business trip in the Regional Secretariat of NTB. The system was built by using CodeIgniter framework with PHP and HTML. The information system of the business trip in Secretary of NTB was made according to assigment letter, warrant official travel and warrant approval tasks. The business trip information system was expected to help the business trip section to create the assigment letter, warrant official travel and warrant approval tasks be better, and to help in the process of data search business trip. Based on the results of the test that have been done on the design of the official travel information system, that was tested to 30 respondents with the percentage of respondents statement of the employee was 44% who chose the statement agree, and 56% strongly agree that selecting statement. While, the percentage of respondents statement from the student with a different question was 53.3% who chose the statement agreed, and 46.7% strongly agree that selecting statement. Keyword : information system, application trip, Regional Secretariat of NTB, governance of official travel, official travel reports.